Comparative Study of Digital and Traditional Marketing Strategies in Increasing Product Sales - Erwanda, Yayang Tineza; Doli, Evika Roma (Smart International Management Journal, 2024)
In recent decades, changes in information and communication technology have revolutionised various sectors, including the business sector. One of the most obvious impacts is the emergence of digital marketing as an alternative to traditional marketing (Rafli, 2022). Traditional marketing, such as print advertising, television, radio, and direct marketing, has been the main choice in promoting products. However, with the development of the internet and social media, digital marketing offers new opportunities that are more scalable and efficient for companies to reach consumers (Chaffey & Ellis-Chadwick, 2019). This research aims to compare the effectiveness of digital and traditional marketing strategies in increasing product sales. The research instruments include a structured questionnaire designed to measure the perceived effectiveness, cost, and conversion rate of each marketing strategy. The sales data collected will be used for statistical analysis, which helps to understand the differences in their effectiveness. The results of this research show that digital marketing strategies have advantages over traditional marketing in increasing sales and customer conversions at a lower cost. Digital marketing strategies increase sales more quickly, efficiently, and consistently compared to traditional marketing methods. These results support contemporary marketing theories that propose the use of technology to assist marketing strategies and decisions. Based on quantitative data showing significant differences in sales achievement, the researcher's assumption that companies in the internet age would better utilise digital marketing strategies was proven correct.